2006
DOI: 10.1111/j.1528-1167.2006.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Contributions of State‐of‐the‐Art Assessment Techniques to Predicting Memory Outcome after Unilateral Anterior Temporal Lobectomy

Abstract: Summary:Purpose: Although anterior temporal lobectomy (ATL) is an effective treatment for many patients with medically refractory temporal lobe epilepsy (TLE), one risk associated with this procedure is postsurgical decline in memory. A substantial number of past studies examined factors that predict memory decline after surgery, but few have investigated multiple predictors simultaneously or considered measures that are currently in use.Methods: This study compared the relative contributions made by presurgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 52 publications
(93 reference statements)
9
83
1
Order By: Relevance
“…There is also evidence that an EZ in or near the hippocampal region but distant from temporal language regions may modulate the lateralization of language representation Hamberger et al, 2007). Compared with patients without HS, patients with HS are more likely to show atypical hemispheric lateralization of language (Pataraia et al, 2004;Powell et al, 2008;Labudda et al, 2010;Richardson, 2010) and have better language functioning (Chelune et al, 1991;Hermann et al, 1995;Davies et al, 1998;Stroup et al, 2003;Gleissner et al, 2004;Baxendale et al, 2006;Lineweaver et al, 2006). As suggested by Knecht (2004), the hippocampus may be crucial to the implementation of hemispheric lateralization for language, and frontotemporal language network functioning may be altered if the hippocampus is injured.…”
Section: Interindividual Factorsmentioning
confidence: 97%
“…There is also evidence that an EZ in or near the hippocampal region but distant from temporal language regions may modulate the lateralization of language representation Hamberger et al, 2007). Compared with patients without HS, patients with HS are more likely to show atypical hemispheric lateralization of language (Pataraia et al, 2004;Powell et al, 2008;Labudda et al, 2010;Richardson, 2010) and have better language functioning (Chelune et al, 1991;Hermann et al, 1995;Davies et al, 1998;Stroup et al, 2003;Gleissner et al, 2004;Baxendale et al, 2006;Lineweaver et al, 2006). As suggested by Knecht (2004), the hippocampus may be crucial to the implementation of hemispheric lateralization for language, and frontotemporal language network functioning may be altered if the hippocampus is injured.…”
Section: Interindividual Factorsmentioning
confidence: 97%
“…Postsurgical visual memory loss after right ATR is predicted by greater presurgical right medial temporal lobe activation in response to a nonverbal task on fMRI, 31 a relatively larger right hippocampus compared with the left hippocampus, 63 later age at seizure onset, 21 and intact presurgical visual memory ability on neuropsychological 20 or Wada testing. 42 Other predictors include side of surgery (nondominant temporal lobe), 15 larger right lateral neocortex and mesial temporal excision, 37 poor postoperative seizure control, 16 and pathology of the resected tissue (atypical hippocampal sclerosis). 65 Besides visual memory, right ATR is found to impair olfactory discrimination, identification, and recognition memory abilities.…”
Section: Memory After Right Atrmentioning
confidence: 99%
“…In Freiburg very few Wada tests have been carried out to assess memory functions prior to surgery. Several studies demonstrated that Wada memory scores did not significantly add more information to postoperative memory prediction as compared to other non-invasive methods or clinical data such as presurgical memory performance or hippocampal volume 5 6 36 37. As recent studies revealed, fMRI may give additional information on postoperative memory loss 38–43…”
Section: Discussionmentioning
confidence: 99%